Measuring of human development through the output-oriented super efficiency vrs. DEA model without inputs - Eren, Miraç; Eren, Murat; Başar, Selim (Serbian Journal of Management, 2017)
The Human Development Index (abbv. HDI) being a popular measure of human well-being has become a measure of human development. However, the HDI has received the major criticisms relating the data structure and the particularly equal weighting scheme. In this study, to eliminate mentioned shortcomings, the measurement of human development was again revisited in the light of data envelopment analysis (DEA). All of the variables used in HDI account were taken as output variables to sort out the relative performance of the countries. In the absence of input variables, and a case in which there are only output variables was reorganized by the formulation of super-efficiency model developed by Andersen and Petersen (1993). The formulation obtained was applied to the Radial based DEA model without inputs, which it is considered as the output of all of the relevant variables, and developed by Lovell and Pastor (1999).